The relationship of Trifolium repens and T. ambiguum with host-specific Rhizobium bacteria for potential incorporation into sustainable, low N input pastures - Truter, Wayne Frederick (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2010.